Incubation temperature alters thermal preference and response to heat stress of broiler chickens along the rearing phase - Morita, V. S. [UNESP] (2016)
The current study aimed to investigate whether embryonic temperature manipulation may alter thermal preference throughout the rearing phase of broiler chickens and how this manipulation may affect response to thermal challenge, metabolism, growth rate and feed intake rate. Eggs were exposed to a constant incubation temperature [machine temperatures: 36 degrees C (Low), 37.5 degrees C (Control), and 39 degrees C (High); eggshell temperature of 37.4 +/- 0.08 degrees C, 37.8 +/- 0.15 degrees C, and 38.8 +/- 0.33 degrees C, respectively] from d 13 till hatching. Low treatment chickens showed lower plasma T3 and GH levels at d 1 of age and lower T3 level at d 42 of age compared to the Control treatment. Preferred ambient, rectal temperature, T4 level, growth rate, food intake rate, and response to thermal challenge were not altered in these chickens. On the other hand, High-treatment chickens exhibited high preferred ambient temperature and rectal temperature during the first 2 wk post-hatch, lower plasma T3 level at d 21 and 42 and a delayed increase in respiratory movement in response to thermal challenge compared to the Control treatment. However, chickens subjected to the Control and High treatments did not differ in T4 and GH level and performance. We conclude that exposure to high temperature during late embryonic development has long-lasting effects on the thermoregulatory system of broiler chickens by affecting the heat tolerance of these chickens. Moreover, the preferred ambient temperature of the chickens from heat-treated eggs correspond to those recommended for the strain under study, whereas for the cold-treated and control-chickens it was 1 degrees C below, indicating that incubation temperature might have consequences on the ambient temperature chickens require during the rearing phase.